Dear friend, from my life I write to you in your life - Li, Yiyun, 1972- (Random House, 2017)
"Yiyun Li's searing personal story of hospitalizations for depression and thoughts of suicide is interlaced with reflections on the solace and affirmations of life and personhood that Li found in reading the journals, diaries, and fiction of other writers: William Trevor, Katherine Mansfield, and more"--